Optimizing the performance of hadoop clusters through efficient cluster management techniques - S. Shraddha Bollamma, K; Manishankar, S; V. Vishnu, M (International Journal of Engineering and Technology, 2018)
The necessity for processing the huge data has become a critical task in the age of Internet, even though data processing has evolved into a next generation level still data processing and information extraction has many problems to solve. With the increase in data size retrieving useful information with a given span of time is a herculean task. The most optimal solution that has been adopted is usage of distributed computing environment supporting data processing involving suitable model architecture with large complex structure. Although processing has achieved good amount of improvement, efficiency, energy utilization and accuracy has been compromised. The research aims to propose an efficient environment for data processing with optimized energy utilization and increased performance. Hadoop environment common and popular among big data processing platform has been chosen as base for enhancement. Creating a multi node Hadoop cluster architecture on top of which an efficient cluster monitor is setup and an algorithm to manage efficiency of the cluster is formulated. Cluster monitor is incorporated with Zoo keeper, Yarn (Node and resource manager). Zoo keeper does the monitoring of cluster nodes of the distributed system and identifies critical performance problems. Yarn plays a vital role in managing the resources efficiently and controlling the nodes with the help of hybrid scheduler algorithm. Thus this integrated platform helps in monitoring the distributed cluster as well as improving the performance of the overall Big Data processing.Â Â Â